Factors predicting willingness to quit snus and cigarette use among young males - Danielsson Maria; Lammi Anelma; Siitonen Simo; Ollgren Jukka; Pylkkänen Liisa; Vasankari Tuula (Nature Publishing Group, 2025)
The health hazards of smoking are well recognised and recently knowledge about the harmful effects of nicotine and snus is accumulating. We investigated the factors increasing the willingness of young Finnish males to quit snus and cigarette smoking. We conducted a questionnaire study conducted in 3 out of 16 Finnish Defence Forces units which included 6508 male conscripts, of whom 4706 responded (response rate 72%, mean age 19.4 years). Factors related to the willingness to quit use were analysed by ordinal regression models. Backward selection following the Akaike information criterion (AIC) was used for the model. The prevalence figures of daily snus use and smoking were 17% and 25%, respectively. 16% of the daily snus users were also daily smokers and 29% were occasional smokers. Multivariate analysis showed that the willingness to quit snus use was associated with the perception of health hazards (OR 3.09, 95% CI 1.94-4.93) and with ≥ 2 quit attempts (OR 3.63, 95% CI 2.44-5.40). The willingness to quit smoking was associated with ≥ 2 quit attempts (OR 3.22, 95% CI 2.32-4.49), and with advice to quit smoking (OR 1.65, 95% CI 1.17-2.32). We created a brief two-question assessment model for snus dependence. With this model, nicotine dependence of daily snus users was congruent with that of nicotine dependence of smokers. A direct comparison with serum cotinine levels is necessary before our assessment model can be used as a proxy for dependence. Regular snus use predisposes to nicotine addiction and accumulated health hazards. Our findings underscore the importance of health promotion efforts in early adolescence and of active support for quitting snus use. Easily applicable tools to estimate nicotine addiction are needed for everyday clinical use.